ANTI-TUBERCULOSIS ACTIVITY OF BIOGENIC SILVER NANOPARTICLES SYNTHESIZED BY USING AQUEOUS LEAF EXTRACT OF LIMONIA ACIDISSIMA L. - BHEEMANAGOUDA N. PATIL,; T. C. TARANATH, (International Journal of Pharma and Bio Sciences, 2016)
Nanoscience and nanotechnology are an emerging area of research focusing on the biosynthesis and application of nanoparticles as there is an urgent need to develop high yielding, low cost, non-toxic and eco-friendly approach for the synthesis of nanoparticles. The present investigation was undertaken to fabricate silver nanoparticles by reducing silver ions and capping of them using leaf broth of Limonia acidissima L. Formation of silver nanoparticles were confirmed by characteristic absorbance peak at 452 nm in UV-Vis spectroscopy. Nanoparticles were characterized by UV-Vis, FTIR, AFM, EDS and HR-TEM. AFM and HR-TEM data revealed that the nanoparticles are spherical in shape and their size ranges between 21-42 nm. Biogenic silver nanoparticles were used to test their efficacy to control the growth of Mycobacterium tuberculosis Zopf, through microplate alamar blue assay (MABA). Tuberculosis (TB) is serious and a life-threatening disease caused by M. tuberculosis (Mtb), which causes a death of about 1.5 million people annually worldwide even though the antibiotics are available. This problem requires the development of novel medicine that can combat disease caused by Mtb. The M. tuberculosis was inhibited by the biogenic silver nanoparticles within the minimum inhibitory concentration (MIC) at 3.12 μg/ml of silver nanoparticles has been recorded from this study.